Improving the Accuracy of Krill Target Strength Using a Shape Catalog - Bairstow, Fiona; Gastauer, Sven; Finley, Luke; Edwards, Tom; Brown, C. Tom A.; Kawaguchi, So; Cox, Martin J. (Frontiers in Marine Science, 2021)
Antarctic krill are subject to precautionary catch limits, based on biomass estimates, to ensure human activities do not adversely impact their important ecological role. Accurate target strength models of individual krill underpin biomass estimates. These models are scaled using measured and estimated distributions of length and orientation. However, while the length distribution of a krill swarm is accessible from net samples, there is currently limited consensus on the method for estimating krill orientation distribution. This leads to a limiting factor in biomass calculations. In this work we consider geometric shape as a variable in target strength calculations and describe a practical method for generating a catalogue of krill shapes. A catalogue of shapes produces a more variable target strength response than an equivalent population of a scale generic shape. Furthermore, using a shape catalogue has the greatest impact on backscattering cross-section (linearised target strength) where the dominant scattering mechanism is mie scattering, irrespective of orientation distribution weighting. We suggest that shape distributions should be used in addition to length and orientation distributions to improve the accuracy of krill biomass estimates.